Hubungan Pengetahuan Dan Sikap Tentang Kanker Payudara Terhadap Pemeriksaan Payudara Sendiri di Dusun Waitasi Kecamatan Kairatu - Andi Herliah; Sumirda Rahareng (STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Cancer Bosom Represent AN Condition Of Where Cell Have Losing Of Operation And Normal Mechanism of him, Quickly And Do Not In Control That Happened At Network Bosom. Method of Peneltian Analytic Descriptive With Approach Of Cross-Sectional Technicsly Random Sample Instrument Research Using Data-Processing Kuesioner With SPSS And Use Test of Chi-Square With This Subyek Peneltian Is Woman Orchard of Waitasi Counted 70 Responder Have Knowledge Whether 41 People 58,6% And Attitude Whether 27 Peop Please Conclude That Ho Refused And Is Ha Accepted By There Are Relation Which Is Disignifikan Among/Between Knowledge And Attitude About Cancer Bosom With Inspection Of Bosom Alone At Woman Orchard of Waitasi.le 38.6% P=003? 0,05 And Relatio Knowledge With Inspection Of Bosom Alone P=0,13? 0,05 Attitude With Inspection Of Bosom Alone Earn.Please Conclude That Ho Refused And Is Ha Accepted By There Are Relation Which Is Disignifikan Among/Between Knowledge And Attitude About Cancer Bosom With Inspection Of Bosom Alone At Woman Orchard of Waitasi.